Room temperature asymmetric negative differential resistance characteristics of AlGaN/GaN resonant tunneling diodes grown by metal-organic chemical vapor deposition. (January 2022) - Yang, Wen-Lu; Yang, Lin-An; Zhang, Xiao-Yu; Li, Yang; Ma, Xiao-Hua; Hao, Yue
Highlights: A large area AlGaN/GaN RTD grown by MOCVD is manufactured. The device adopts air-bridge structure suitable for the terahertz (THz) band. NDR characteristics of the RTD are observed under bipolar bias at room temperature. The enhancement of the reverse NDR performance is theoretically investigated. The reproducible NDR characteristics of the RTD are reported under bipolar bias. Abstract: A large area AlGaN/GaN resonant tunneling diode (RTD) grown by metal–organic chemical vapor deposition (MOCVD) is manufactured. The device adopts air-bridge structure suitable for the terahertz (THz) band, and a commercially available high-frequency GaN technology is applied in the process of device fabrication. Negative differential resistance (NDR) characteristics of the device are observed under the bipolar bias voltage at room temperature, which exhibits clear anti-symmetry in the peak-to-valley current ratio (PVCR), peak voltage and peak current density. The work systematically investigates how the built-in electric field introduced by polarization effects modulates the resonant tunneling transport utilizing TCAD tool Silvaco-ATLAS, and analyzes the enhancement of the resonant tunneling under negative bias voltage of the RTD with low-aluminum content AlGaN as barriers. The AlGaN/GaN RTD with conventional double-barrier single (DBS) quantum well (QW) structure shows reproducible NDR characteristics under the bipolar bias voltage at room temperature, which facilitates the design and extensive study of complicated device structures.